The Effect of Inflation, Exchange Rate and Credit Risk on Banking Profitability in Indonesia (2021 – 2024) - Rismatur Reza Tri Auliana; Choirul Hana (International Publisher (YAPENBI), 2025)
This study aims to analyze the influence of inflation, credit risk, and exchange rates on banking profitability in Indonesia, which is an important issue in a dynamic economic context. Measured by ROA with the period 2021-2024 based on Signaling theory. By understanding whether these macroeconomic factors can affect the bank's financial performance. Using quantitative methods, multiple linear regression was conducted through SPSS 16, with secondary data from 11 large conventional banks on the IDX and produced 44 observations. As a result, simultaneously, inflation, exchange rates, credit risk affect banking profitability significantly are shown by the results (F = 3.123, p = 0.036), explaining the 15.4% variation (R² = 0.154; Adjusted R² = 0.106), but only a fraction of the credit risk (t = 2.618, p = 0.012, β = 0.051) was affected. inflation (t = 0.975, p = 0.335) and exchange rate (t = 0.995, p = 0.326) are not. These findings contribute to understanding the importance of risk control in maintaining bank profitability amid uncertain economic conditions, emphasizing the priority of internal credit risk management over external macroeconomic signals in post-pandemic banking stability. The recommendations include stricter supervision of NPLs by the OJK and BI, as well as hedging for exchange rate risks. The conclusions of this study emphasize the need for banks to improve risk management and transparency of financial statements, further research is recommended to examine other factors besides the variables in this study.